Field report PAC 671: Global Finance Centre Baker Hughes / Nur Husnina Thurayya Mohd Jamil - Mohd Jamil, Nur Husnina Thurayya (Universiti Teknologi MARA, Terengganu, 2024)
Baker Hughes Company, an American energy company based in Houston, Texas, is one of the world's largest energy and oilfield services companies. It provides the global oil and natural gas industry with products and services for drilling, formation evaluation, completion, and production. Baker Hughes stands out as the only major oilfield service company structured around strong product-line divisions focused on Best-in-Class products and services. Additionally, Baker Hughes offers the broadest portfolio of technology solutions for energy and industry, which includes Industrial and Energy Technology (IET), Oilfield Services and Equipment (OFSE), Digital Solutions, and Turbomachinery and Process Solutions (TPS). The company operates in over 120 countries worldwide namely six regions such as Asia Pacific, Sub-Saharan Africa, Middle East, Europe, North America and Latin America.